Personal Academic Websites Serving Scholarly Work Purpose - Ciriminna, Rosaria; Pagliaro, Mario (Journal of Data Science, Informetrics, and Citation Studies)
A personal academic website is a space on the World Wide Web through which a scholar proactively communicates her/his activities in research, education and societal service to the public. Is having such website worth the effort? Does a personal website provide real benefits to the scholarly activities of a researcher and educator? And, if yes, why and how? Referring to selected examples, this study shows how a personal academic website can serve the overall purpose of scholarly work, independently of the disciplinary field.
Keywords: Personal academic website; Self-archiving; green open access; Scholarly work; Impactful research.